Potential antagonistic rhizobacteria to control Colletotrichum scovillei, the cause of anthracnose disease in chili pepper - Dewa Ngurah Suprapta; Anak Agung Ketut Darmadi; Khamdan Khalimi (Society for Indonesian Biodiversity, 2020)
Abstract. Darmadi AAK, Suprapta DN, Khalimi K. 2020. Potential antagonistic rhizobacteria to control Colletotrichum scovillei, the cause of anthracnose disease in chili pepper. Biodiversitas 21: 2727-2734. Six species of Colletotrichum were identified as the cause of anthracnose disease on Bali Island, Indonesia in 2018. These species were C. scovillei, C. acutatum, C. nymphaeae, C. gloesporioides, C. truncatum, and C. fructicola. Among them, C. scovillei was the most prevalent at 55% of all samples tested. This study was conducted to find potential antagonistic rhizobacteria isolated from various rhizospheres of plants grown in Bali. A total of 1,040 rhizobacteria isolates were tested for their antagonistic activity against the growth of C. scovillei on potato dextrose agar. Results showed that 10 isolates inhibited the growth of C. scovillei by more than 80%. Among these isolates C1 and C7B possessed inhibitory activity at 94.9% and 94.3%, respectively. Molecular identification based on analysis of 16S rRNA gene showed that isolate C1 belonged to the species Paenibacillus polymyxa, whereas isolate C7B was identified as Bacillus siamensis. According to scanning electron serious damage on mycelia of C. scovillei was observed. Wrinkles were observed on mycelia of C. scovillei grown jointly with rhizobacterial isolate C1, whereas no wrinkle was observed on C. scovillei grown solely. Three compounds were detected in the hexane phase of cell-free filtrate P. polymyxa C1, namely, 3-hydroxy-2-butanone and 2,3-butanediol. These compounds may be responsible for antifungal activity against C. scovillei.